The Arc of Modernization: Economic Structure, Materialism, and the Onset of Civil Conflict. Issue 2 (9th June 2016) - Chatagnier, J. Tyson; Castelli, Emanuele
Abstract : The onset of intrastate conflict has two requisite conditions: that prospective insurgents have an incentive to rebel, and that the state lacks the capacity to deter such a rebellion. We outline a simple rationalist argument grounded in gains from economic growth—to both individual income and state revenue—to argue that modernization has the potential to affect the likelihood of civil conflict through both of these conditions. The shift away from a rent-seeking economy affects opportunity costs for rebellion by increasing the cost of recruitment, broadening the time horizon for gain, and decreasing looting possibilities. On the state side, modernization increases state military, economic, and institutional capacity, allowing governments to deter rebellion. We construct an index of modernization from World Bank data and apply a strategic model to explore the effect of modernization on both states and rebels simultaneously. We find that the modernization process describes an arc that may increase the likelihood of unrest in the early stages, but has long-term stabilizing effects.